Effect of inflammatory bowel diseases on household chores - Mattila Kalle; Rankala Rasmus; Voutilainen Markku; Mustonen Anssi (WILEY, 2025)
More than a half of inflammatory bowel disease (IBD) patients experienced a moderate negative effect on their household chores due to their IBD. The negative effect was more common amongst women.